Protein enrichment of palm kernel cake. - Musa, Mohd. Hanafi (2001)
The invention discloses a method of enhancing the protein content of palm kernel cake (PKC) comprising the steps of sterilizing PKC resulting in a moisture of at least 60ww, inoculating the resultant product with fungi selected from the fungus trichoderma or fungus sclerotium rolfsii or fungus aspergillus niger or in combination of one or more and maintaining the inoculated PKC at a temperature of 20 - 35Â°c for a period of 5 to 12 days. The sterizilation of PKC can be either by subjecting the PKC to steam, to peroxides or to acetic acid/sodium chlorite. Preferably 1-3 5 ww of fungi is used to inoculate the PKC. The trichoderma fungiis selected from the group consisting of Trichoderma harzianum, Trichoderma longibrachiatium or Trichoderma koninggi. The protein enchanced PKC is used as a component in animal feed meal.